Fossil Leaves of Meliosma (Sabiaceae) With Associated Pollen and a Eupodid Mite From the Eocene of Maoming Basin, South China - Moiseeva, Maria G.; Kodrul, Tatiana M.; Tekleva, Maria V.; Maslova, Natalia P.; Wu, Xinkai; Jin, Jianhua (Frontiers in Ecology and Evolution, 2022)
A first occurrence of the genus Meliosma (Sabiaceae) is reported from the upper Eocene of the Maoming Basin of South China. This fossil is one of the oldest reliable records of the genus within its modern center of diversity. Fossil leaves are assigned to a new species, Meliosma eosinica sp. nov. based on leaf morphology and epidermal characters. The leaf epidermal anatomy of fossil Meliosma is illustrated for the first time. We also provide the first SEM observation of pollen grains associated with Meliosma. This study also documents an occurrence of mites within leaf domatia previously unknown from the fossil record. We presume that the studied mite belongs to the superfamily Eupodoidea (Arthropoda), and probably the family Eupodidae, which comprises very small soft-bodied cosmopolitan mites occupying a wide range of terrestrial habitats. Additionally, we analyze damage types on the fossil leaves of Meliosma. They exhibit exclusively external foliage feeding damage caused by arthropods and traces of probable fungal infection. A review of currently known fossil occurrences of leaves, fruits, and wood of Meliosma provides evidence for the geological and geographical distribution of the genus.